The influence of google sites digital media with a STEM approach on student learning outcomes in plant material - Safrina, Nura; Novita, Rita; Sariakin, Sariakin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to examine the effect of implementing Google Sites Digital Media with a STEM Approach as an Effort to Improve Student Learning Outcomes on Plant Material. The study used a pre-experimental design with a one-group model, namely pre-test and post-test, which was implemented in grade IV of SD Negeri 48. Data were collected through a multiple-choice test of 25 questions that measured students' understanding of plant material. At the beginning of the study, students took a pre-test to determine their initial abilities. Next, learning was carried out using Google Sites media that was designed interactively by integrating text, images, videos, simulations, and simple STEM-based project assignments. The learning process encouraged students to explore plant concepts scientifically, utilize digital technology, solve problems, and apply mathematical concepts in real contexts. After the treatment, students took a post-test to measure improvements in learning outcomes. The results showed a significant increase in the average post-test score compared to the pre-test, with the Wilcoxon Signed Ranks Test obtaining a significance value of 0.000. These findings prove that interactive digital learning media based on Google Sites with a STEM approach is effective in improving students' conceptual understanding and learning outcomes. The use of this media is recommended as a learning strategy that is worthy of being developed and implemented in science learning in schools